Grand Rapids - 03 - (Author); (Interviewer); (Publisher)
Photograph - A scow on the Grand Rapids. A note on the back reads: Scow running down the Grand Rapids on the Athabasca River. This was one of the worst ones on the river from Athabasca Landing to McMurray